(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article talks about the virtues of the Companions, that the differences between them are a blessing and an example for the next Ummah, that despite the dispute between Ali and Muawiya, may Allah be pleased with them, they always respected each other, and that the feelings of friendship and brotherhood are high.